Europe's entry into the venture capital business: efficiency and policy - Michael Stolpe (Kiel Institute for World Economics (IfW), 2004)
This paper provides new evidence on Europe's experience with venture capital in the 1990s. Individual countries' activity is not solely determined by country characteristics and a purely domestic history, but also by a common European experience: the interdependence of valuations in primary equity markets. Each country must seek to improve the efficiency of its venture capital sector independently. Specific policies should depend on initial conditions and on the evolution of micro-efficiency. Initial public offerings backed by venture capital provide the appropriate window to look at the relative efficiency of individual venture capital organizations and their learning process over time. This paper is part of the international research programme on European Integration, Financial Systems and Corporate Performance (EIFC) carried out within the European Commission's specific programme "Improving the Human Research Potential and the Socio-Economic Knowledge Base". A first draft was discussed at the final EIFC programme workshop held on February 23, 2004, at the Kiel Institute for World Economics.
Keywords: 330; Risikokapital; Internationaler Preiszusammenhang; Spillover-Effekt; Wirtschaftliche Effizienz; Wertpapieremission; Schätzung; EU-Staaten; Deutschland; Frankreich